La autenticación y certificación de las firmas electrónicas como atribución de los notarios dentro de un entorno digital en los actos notariales - Gárate Calderón, Nabila María (2025)
This article aims to conduct a critical legal analysis of the authentication and certification of electronic signatures as a responsibility of notaries within a digital environment. In developing this article, a thorough review of legal doctrine, jurisprudence, and relevant regulations was conducted to understand the historical evolution, theoretical principles, and legal practices regarding electronic signatures within the powers of notaries. Direct interviews were conducted with notaries in Guayaquil, as well as with professionals specializing in notarial matters, to understand notarial practice and their opinions as professionals in the field. It was evident that there is a lack of regulations that allow the use of technological tools and platforms, guaranteeing compliance with the notarial principles that govern the Ecuadorian system, to implement electronic signatures within the powers of notaries. The article concludes that it is necessary to reform the notarial law, the e-commerce law, the data law, and related laws regarding the use of electronic signatures, as well as the regulations related to the requirements to be a notary in Ecuador. Furthermore, it requires the active participation of the Ecuadorian state in the financing and implementation of legal/technological platforms that guarantee the use of electronic signatures within notarial acts in Ecuador, the effective compliance with notarial principles, formality, legality, and legal and information security for users and notaries as officials who attest public authority within their powers.